DAYA PREDASI CECOPET (Forficula auricularia) (Dermaptera : Nisolabididae) PADA BERBAGAI INSTAR LARVA ULAT GRAYAK (Spodoptera litura F.) (Lepidoptera : Noctuidae) DI LABORATORIUM - Yasir Arobi; Syahrial Oemry; Fatimah Zahara (Universitas Sumatera Utara, 2013)
The Ability of Cecopet (Forficula auricularia) (Dermaptera: Nisolabididae) on some Instar of Spodoptera litura F. (Lepidoptera: Noctuidae) in the Laboratory. The objective was to study the ability of Cecopet (F. auricularia) on some instar of S. litura. The research conducted at the Insect Laboratory, Faculty of Agriculture, University of Sumatera Utara, Medan, from Agustus to September 2012. The method of this research was Randomized Complete Design Non Factorial with eight treatments (control with 2st and 4th instar, 2 males cecopet, 2 female cecopet, a pair on 10 larvae 2nd and 4th instar/stoples) with three replications.The results showed that the highest percentage of mortality was C2 (2 female cecopet on 10 larvae/ stoples) is 96,67% and the lowest was C02 (control with 4th instar) is 0%. Keywords : Forficula auricularia, Spodoptera litura, mortality